Diversity within the Redeye Bass, Micropterus coosae (Perciformes: Centrarchidae) species group, with descriptions of four new species - Baker, Winston H.; Blanton, Rebecca E.; Johnston, Carol E. (Zootaxa, 2013)
The Redeye Bass, Micropterus coosae, was described from the Mobile River basin, Chattahoochee, and Savannah rivers in Alabama and Georgia, USA, by Hubbs and Bailey (1940). At that time the authors recognized significant variation in the Black Warrior River population, and noted that with further study this form may be recognized as a separate taxon. An examination of variation in morphology and mitochondrial DNA supported this observation, and highlighted additional species-level variation, resulting in descriptions of a total of four new species: Micropterus cahabae, new sp., restricted to the Cahaba River system; Micropterus tallapoosae, new sp., restricted to the Tallapoosa River system; Micropterus warriorensis, new sp., from the Black Warrior River system; and Micropterus chattahoochae, new sp., from the Chattahoochee River system. Micropterus coosae is restricted to the Coosa River system. The new species differ from each other and from M. coosae by a combination of pigmentation and scale count characteristics, development of the tooth patch, and divergence within the ND2 gene. While two of these species are relatively common in upland streams within their ranges, M. warriorensis, M. cahabae and M. chattahoochae are uncommon and may warrant protection.